2016
DOI: 10.1021/acs.nanolett.6b02577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cage Shape on Nanoparticle-Based Drug Carriers: Anticancer Drug Release and Efficacy via Receptor Blockade Using Dextran-Coated Iron Oxide Nanocages

Abstract: Although a range of nanoparticles have been developed as drug delivery systems in cancer therapeutics, this approach faces several important challenges concerning nanocarrier circulation, clearance, and penetration. The impact of reducing nanoparticle size on penetration through leaky blood vessels around tumor microenvironments via enhanced permeability and retention (EPR) effect has been extensively examined. Recent research has also investigated the effect of nanoparticle shape on circulation and target bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…More interestingly, cage‐structured iron oxide nanoparticles loading Riluzole, a cell membrane pathway inhibitor, increased the propensity of cytotoxicity to metastatic cancer cells in comparison with spherical one owing to the high payload and the membrane localization . They found that the more positively charged spherical nanoparticles are internalized in a shorter time than the nanocages with negative charges, thus the negatively charged nanocages more efficiently block the membrane pathway.…”
Section: Key Features Of Nanoparticles Required For Efficient Cancer mentioning
confidence: 99%
“…More interestingly, cage‐structured iron oxide nanoparticles loading Riluzole, a cell membrane pathway inhibitor, increased the propensity of cytotoxicity to metastatic cancer cells in comparison with spherical one owing to the high payload and the membrane localization . They found that the more positively charged spherical nanoparticles are internalized in a shorter time than the nanocages with negative charges, thus the negatively charged nanocages more efficiently block the membrane pathway.…”
Section: Key Features Of Nanoparticles Required For Efficient Cancer mentioning
confidence: 99%
“…For particles smaller than 100 nm, spherical shaped NPs show the highest cell uptake 91 . In a study, the effect of NC structures on localization of nanocarriers in and around the cells and their cellular uptake was investigated by Rampersaud et al 92 . Here, longer dwell-time of NPs at the outer membrane of cancer cells was a priority to effectively release the ion channel blocking agent.…”
Section: - Modification and Targeting Approaches For Nc Ddssmentioning
confidence: 99%
“…This difference was proposed to be related to the charge-screening effect of NC surface. Riluzole inhibited the secretion of glutamate by cancer cells via blocking the sodium ion channels, leading to prevention of glutamate receptor activation, thus lowering cancer cell growth (Figure 3-a) 92 . Particle surface charge also plays a significant role in NP-cell interactions and cell uptake.…”
Section: - Modification and Targeting Approaches For Nc Ddssmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicochemical features including size, shape, surface functionalization, and dispersion state of nanoparticles would all affect their performances . Gold nanocaps or semishells demonstrate novel plasmonic and optical properties due to the presence of unique cavities within gold nanoparticles .…”
Section: Introductionmentioning
confidence: 99%